Wireless Security Protocols WPA3: A Systematic Literature Review - Asmaa Halbouni; Lee-Yeng Ong; Meng-Chew Leow (IEEE Access, 2023)
The size of wireless networks and the number of wireless devices are growing daily. A crucial part of wireless security involves preventing unauthorized access by using wireless security protocols in order to protect the data in wireless networks. In 2018, Wi-Fi Protected Access 3 (WPA3) was ratified to protect the data in devices bearing the Wi-Fi trademark. WPA3 has many security improvements over previous wireless security protocols, by providing a better encryption method and key sharing. In this paper, a Systematic Literature Review (SLR) was conducted to analyze three aspects of WPA3 protocol: the reasons behind the release of WPA3, the encryption methods and mode of operation in this protocol, and the attacks that remain penetrating WPA3. In this review, thirty-six articles were identified as the selected research articles, written between 2018 and 2023, focusing mainly on WPA3. After the analysis of the selected articles, the encryption methods and modes of operation were presented in the SLR. In addition, the vulnerabilities that the WPA3 protocol solved and the ones that remain unsolved were discussed. This study concluded that WPA3 excels over its predecessors by providing more security and reliability to wireless networks. The result of this SLR of WPA3 proposes two methods that seek to increase the security level of WPA3 networks, which has been discussed in the discussion section.